PEMBINAAN CABANG OLAHRAGA SEPAKBOLA PADA SSB RAJAWALI PEKANBARU - Malik, Abdul; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study is to provide information to coaches, coaches, athletes, the community, and related agencies, especially football fans, regarding the development of soccer sports achievements, especially at SSB Rajawali Pekanbaru. This research was conducted using a descriptive quantitative research that describes a symptom, an event, an incident that is happening at the present time, how is the level of football development at SSB Rajawali Pekanbaru. Based on the results of the research and discussion that the author has described in the previous chapter, it can be concluded from the results of the analysis of coach quality data that it can be seen that the quality level of the football coach at SSB Rajawali Pekanbaru which is in the very good category is 30 people of 83.3%, while in the good category, 5 people were 13.9%, for the enough category 1 person with a frequency of 2.8%. Furthermore, the results of the analysis of the athlete's motivation data, it can be seen that the level of motivation of athletes in the soccer sport at SSB Rajawali Pekanbaru which is in the very good category is 72.2%, while in the good category 9 is good by 25%, for the enough category 1 person with a frequency of 2.8%. Based on the results of the analysis, the motivation level of football athletes at SSB Rajawali Pekanbaru is in the very good category with an average result of 79.76%. Then the results of the data analysis of facilities and infrastructure can be seen that the level of quality of athletes in the soccer sport at SSB Rajawali Pekanbaru which is categorized as very good 19 people is 52.8%, while in the good category 15 is good by 41.7%, for the category is quite 2 people with frequency of 5,6%. Based on the results of the analysis, the level of facilities and infrastructure for the football sport at SSB Rajawali Pekanbaru is in the good category with an average result of 74.75%. Key Words: Football Sports Development, SSB Rajawali Pekanbaru